2016
DOI: 10.1017/s1049023x16000078
|View full text |Cite
|
Sign up to set email alerts
|

Are Tertiary Care Paediatricians Prepared for Disaster Situations?

Abstract: Despite a clear perception of the risks and a high willingness to work, preparedness is limited. The major conclusion is that basics of disaster management should be included in pediatric training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Each have their advantages and disadvantages and, when employed together, can synergistically improve hospital personnel preparedness. Even among tertiary care pediatricians, only 35 % of surveyed responders in a recent international study had disaster training, whereas 53 % felt it should be an obligatory part of their curriculum [14]. Pediatric-specific training should be incorporated in all disaster plans, as even adult centers will receive pediatric patients during a mass casualty.…”
Section: Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Each have their advantages and disadvantages and, when employed together, can synergistically improve hospital personnel preparedness. Even among tertiary care pediatricians, only 35 % of surveyed responders in a recent international study had disaster training, whereas 53 % felt it should be an obligatory part of their curriculum [14]. Pediatric-specific training should be incorporated in all disaster plans, as even adult centers will receive pediatric patients during a mass casualty.…”
Section: Preparationmentioning
confidence: 99%
“…They found that whereas 95 % of responders anticipated receiving pediatric patients after a mass casualty event, only 44 % of these hospitals had specific emphasis on the pediatric patient as part of their disaster plan [14]. Approximately 50 % of the hospitals had the ability to mobilize pediatric personnel, open pediatric intensive care beds, acquire specific pediatric intensive care supplies, accommodate for isolation, and have access to pediatric subspecialty physicians.…”
Section: Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for more systematic measures applied is corroborated by the research showing the lack thereof. For example, [ 10 ] show that regular medical students are not prepared to deal with emergency situations, such as natural disasters consequences, as opposed to those who studied medicine in a military school. The same unpreparedness of health professionals to deal with emergencies, ranging from lack of knowledge of protocols and their implementation, was also found in Saudi Arabia, China, and Egypt [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The following are available online at , Table S1: The main global information collected from the publications. [ 8 , 10 , 11 , 12 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ,…”
mentioning
confidence: 99%